(untitled) (Global Journal of Human-Social Science, 2021)
Without mincing words there is a gradual loss of long-aged tradition a method of equipping young ones for life In Yor b traditional setting the teaching of Yor b numerals remains an authentic means of transmitting culture from one generation to another This paper attempts to examine that Yor b traditional education is deeply rooted in Yor b orature Equally it shows that the education system had been part and parcel of the society and it is not the training given in modern education but education which the indigenous black people of Africa offered Additionally the paper establishes that Yor b orature serves both recreational as well as educational purposes to prove that the use of Yor b orature is a fundamental basis for teaching the young ones the Yor b numerals as embedded in the culture and tradition of the people Apart from this immediate and apparent function of teaching the young ones the teaching of Yor b numerals initiates child ren into the various phases of life This research work adopted both primary and secondary research methods